2004
DOI: 10.1002/anie.200353541
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Monomeric [LAl(NH2)2]—A Main‐Group Metal Diamide Containing Two Terminal NH2 Groups

Abstract: Dedicated to Professor Dietmar Seyferth on the occasion of his 75th birthdayAluminum amides supported by organic ligands are important molecular precursors for the preparation of aluminum nitrides, such as Al À N based semiconductors and Al À N ceramics.[1] Amides with the general formula [R 2 Al(NH 2 )], in which R corresponds to an organic substituent, are rare. The presence of a reactive NH 2 group, which can be involved in further substitution reactions, may lead to mixed-metal imides that have the AlÀN(H)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 22 publications
2
40
0
1
Order By: Relevance
“…The presence of the NH moiety was further confirmed by IR spectroscopy. In compounds 1-4 and 7, the corresponding vibrations were found in a narrow interval ν = 3371-3381 cm -1 , which is in a good agreement with the ν s vibration of the NH 2 group in LAl(NH 2 ) 2 (ν = 3396 cm -1 ) [21] and LGa(NH 2 ) 2 (ν = 3373 cm -1 ). [8] In cases of compounds 5 and 6, the matching vibrations were found at lower wavenumbers [ν = 3338 (for 5), 3335 cm -1 (for 6)].…”
Section: -8supporting
confidence: 76%
See 1 more Smart Citation
“…The presence of the NH moiety was further confirmed by IR spectroscopy. In compounds 1-4 and 7, the corresponding vibrations were found in a narrow interval ν = 3371-3381 cm -1 , which is in a good agreement with the ν s vibration of the NH 2 group in LAl(NH 2 ) 2 (ν = 3396 cm -1 ) [21] and LGa(NH 2 ) 2 (ν = 3373 cm -1 ). [8] In cases of compounds 5 and 6, the matching vibrations were found at lower wavenumbers [ν = 3338 (for 5), 3335 cm -1 (for 6)].…”
Section: -8supporting
confidence: 76%
“…This is supported by the planar environment of the N3 and N4 atoms in 4. The corresponding signal of the N-H proton in compounds 1-3 and 7 appears at lower field than the signal for the N-H protons in LAl(NH 2 ) 2 (δ = -0.52 ppm) [21] and LGa(NH 2 ) 2 (δ = -0.58 ppm), but at higher field compared to those in 5 and 6. The latter is caused by the presence of the chlorine atom attached to the same metallic center as the amino group.…”
Section: -8mentioning
confidence: 76%
“…Additionally, the steric property of the ligand works synergetically to its electronic factors offering an unique possibility to stabilize the low coordination number at the metal center or low oxidation states [31,[52][53][54]. The mono-and dihalides of Al and Ga synthesized recently by our group are interesting compounds and have been utilized to prepare the corresponding hydroxides [12,14], thiols [49], and amides [55]. Similarly we have also shown that the metathesis reaction of these compounds with suitable fluorinating agents can lead to the formation of the corresponding fluorine derivatives [56].…”
Section: Group 13 B-diketiminate Fluoridesmentioning
confidence: 98%
“…These compounds were found to be stable at ambient conditions and successfully applied as precursors for heterobimetallic species and alumoxanes [10][11][12]. The reaction of (L)AlCl 2 or (L)Al(I)Cl with stoichiometric amounts of water in the presence of N-heterocyclic carbene was previously used for preparation of aluminum hydroxides such as (L)Al(OH) 2 and [(L)Al-(l-OH)Cl] 2 [13][14][15]. These very sophisticated and complicated procedures cause that the synthesis of hydroxyaluminum compounds still is considered as a challenge.…”
Section: Introductionmentioning
confidence: 98%